The Tumor-Selective Cytotoxic Agent β-Lapachone is a Potent Inhibitor of IDO1. (January 2013) - Flick, Hollie E.; LaLonde, Judith M.; Malachowski, William P.; Muller, Alexander J.
Β-lapachone is a naturally occurring 1, 2-naphthoquinone-based compound that has been advanced into clinical trials based on its tumor-selective cytotoxic properties. Previously, we focused on the related 1, 4-naphthoquinone pharmacophore as a basic core structure for developing a series of potent indoleamine 2, 3-dioxygenase 1 (IDO1) enzyme inhibitors. In this study, we identified IDO1 inhibitory activity as a previously unrecognized attribute of the clinical candidate β-lapachone. Enzyme kinetics-based analysis of β-lapachone indicated an uncompetitive mode of inhibition, while computational modeling predicted binding within the IDO1 active site consistent with other naphthoquinone derivatives. Inhibition of IDO1 has previously been shown to breach the pathogenic tolerization that constrains the immune system from being able to mount an effective anti-tumor response. Thus, the finding that β-lapachone has IDO1 inhibitory activity adds a new dimension to its potential utility as an anti-cancer agent distinct from its cytotoxic properties, and suggests that a synergistic benefit can be achieved from its combined cytotoxic and immunologic effects.